ARUS KAS UNTUK MENDETEKSI MANIPULASI AKTIVITAS RIIL DAN DAMPAKNYA TERHADAP KINERJA PASAR - Melina Djauhari; Elsa Imelda (Jurnal Paradigma Akuntansi, 2022)
This study aims to determine whether real activity manipulation can be detected through operating cash flow and how the effect of real activity manipulation on market performance in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. The sample was selected using purposive sampling method and the valid data was 152 data. Data processing techniques using panel data regression analysis assisted by the EViews program (Econometrical Views) version 10. The results of this study indicate that real activity manipulation can be detected through operating cash flow and real activity manipulation has a significant positive effect on market performance. The implication of this study are investors can conduct a more in-depth evaluation of the market performance of a company before making an investment decision and this research can be a reference or consideration for company managers who wish to carry out earning management, especially through real activitiy manipulation.